Proteomic identification of galectin‐3 binding ligands and characterization of galectin‐3 proteolytic cleavage in human prostasomes. (9th July 2013) - Kovak, M. R.; Saraswati, S.; Goddard, S. D.; Diekman, A. B.
Summary: Galectin‐3 is a multifunctional carbohydrate‐binding protein that was previously characterized as a proteolytic substrate for prostate‐specific antigen (PSA) and was shown to be associated with prostasomes in human semen. Prostasomes are exosome‐like vesicles that are secreted by the prostatic epithelium and have multiple proposed functions in normal reproduction and prostate cancer. In the current study, galectin‐3 binding ligands in human prostasomes were identified and characterized with the goal to investigate galectin‐3 function in prostasomes. Galectin‐3 binding proteins were isolated by affinity column chromatography. Candidate ligands identified by MS/MS were PSA, prostatic acid phosphatase (PAP), zinc alpha‐2‐glycoprotein (ZAG), dipeptidyl peptidase‐4 (CD26), aminopeptidase N (CD13), neprilysin, clusterin, antibacterial protein (FALL‐39) and alpha‐1‐acid glycoprotein (ORM1). Biochemical methods were used to characterize the ability of galectin‐3 to bind to selected ligands, and galectin‐3 cleavage assays were utilized to investigate the protease(s) in prostasomes that cleaves galectin‐3. CD26, CD13, PSA, PAP and ZAG immunoreactivity were detected in extracts of purified prostasomes. One‐dimensional electroblot analysis of prostasomes demonstrated that CD26, PAP and CD13 immunoreactivity co‐migrated with galectin‐3‐reactive protein bands. PSA and ZAG were found to be associated with the surface of prostasomes. Both intact and cleaved galectin‐3 were detected in prostate and prostasome extracts. Cleavage and inhibition assays indicated that PSA in prostasomes proteolytically cleaves galectin‐3. The identification of these glycoproteins as galectin‐3 ligands lays the groundwork for future studies of galectin‐3 and prostasome function in reproduction and prostate cancer.